2021
DOI: 10.1111/rda.13951
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles of pre‐pubertal and adult in vitro matured ovine oocytes obtained from FSH‐stimulated animals

Abstract: Harvesting of oocytes from pre-pubertal female livestock for in vitro embryo production is a process known as Juvenile in vitro Embryo Transfer (JIVET). The incorporation of JIVET into breeding programmes is beneficial because it reduces generation spacing and increases genetic gain rates. Prepubertal females produce more oocytes than adult individuals (Paramio & Izquierdo, 2014). However, JIVET is limited by the low developmental capacity of pre-pubertal oocytes and low capacity for embryonic development afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…PRELID3B has an important role in excessive melanin deposition ( 61 ) and regulates lipid accumulation in mitochondria ( 62 ). In lamb MII oocytes, down-regulation of ATP5E and up-regulation of CUL1 , MARCH7 , and TRIM17 might cause low competence of lamb embryos ( 63 ). Furthermore, it has been reported that ATP5E is a promising candidate biomarker for oocyte viability after IVM ( 64 ), so the gene might be associated with reproductive traits in female animals.…”
Section: Discussionmentioning
confidence: 99%
“…PRELID3B has an important role in excessive melanin deposition ( 61 ) and regulates lipid accumulation in mitochondria ( 62 ). In lamb MII oocytes, down-regulation of ATP5E and up-regulation of CUL1 , MARCH7 , and TRIM17 might cause low competence of lamb embryos ( 63 ). Furthermore, it has been reported that ATP5E is a promising candidate biomarker for oocyte viability after IVM ( 64 ), so the gene might be associated with reproductive traits in female animals.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HUMSCs of preterm infants may be precursor cells of other cell subsets. Nestin expression was detected in C12, C6, C8, and C10, indicating that it plays a crucial role in maintaining HUMSCs in a low differentiation state and is also considered one of the markers of early cell differentiation, [19] as evidenced by the distribution of Nestin (+) cells closer to the starting point on the pseudo-curve(Fig. 4B,4C).…”
Section: Trajectory Inferencementioning
confidence: 93%
“…C1 and C14, which mainly from BMSCs, Were high expressed genes of GNB2L1, ATP5E, and PENK, associate with oxidative phosphorylation, cell growth, migration and differentiation. [19,20]C2 was high expressed of SQSTM1, KRT19, NDUFA13, relate to epithelial cell structure, cell proliferation and mitochondrial respiratory chain, [21][22][23] C3 and C16 share differential factors (NPPB, CRYAB, and ACTG2) involved in cellular ATP release, protects cardiomyocytes, and muscle regulation. [24][25][26] Differential genes in C5 (SAA1, SYNPO2, NEAT1) relate to in ammation and cancer inhibition, [27][28][29] while C6 genes (TOP2A,, MKI67, CENPF) associate with staining structure and cell proliferation.…”
Section: Differential Gene Analysismentioning
confidence: 99%
“…No differences in blastocyst development were found between stimulated and unstimulated lambs (O'Brien et al., 1997 ). Such a reduced developmental potential is related to morphological and functional alterations (Ledda et al., 2001 ; Leoni et al., 2007 ; O'Brien et al., 1996 ; Ying et al., 2021 ). In the perspective of exploiting the large JIVET potential, the availability of predictive markers on good developmental ability has been investigated.…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%